Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Rumah Sakit Akademis Jaury Jusuf Putera Makassar - Muh. Gibran Syahrum; Andi Mustika Amin; Abdi Akbar Idris; Chalid Imran Musa; Muh. Ikhwan Maulana Haeruddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research aims to determine the effect of workload on performance, the effect of the work environment on performance and the effect of workload and work environment on employee performance at the Jaury Jusuf Putera Makassar Academic Hospital. The type of data used in this research is quantitative data obtained from questionnaires that have been distributed and relate to the problem being studied with a sample size of 47 people. The results of the research show that the workload variable has a significant level of 0.005, which is smaller than 0.05 with a coefficient value of -0.03 indicating that the influence it has is negative on the independent variable. Meanwhile, the work environment variable has a significance level of 0.000 with a coefficient value of 0.044 indicating that the influence given is positive on the independent variable.